DENSITY AND CORRELATION INTEGRALS IN DEEP-INELASTIC MUON-NUCLEON SCATTERING AT 490 GEV - Adams, M; Aid, S; Anthony, P; Baker, M; Bartlett, J; Bhatti, A; Botterweck, F; Braun, H; Busza, W; Conrad, J; Coutrakon, G; Davisson, R; et al. (1994)
Results on density integrals Fq(Q2) and correlation integrals Kq(Q2) are presented for the first time in muon-nucleon scattering at ∼ 490 GeV, using data from the E665 experiment at the Tevatron of Fermilab. A clear rise of the Fq integrals with decreasing size of the phase-space cells ("intermittency") is observed for pairs and triplets of negative hadrons whereas the effect is much weaker for mixed charge combinations. From these findings it is concluded that the observed intermittency signal is mainly caused by Bose-Einstein interference. Furthermore, no energy (W) dependence of F2(Q2) is observed within the W range of the E665 experiment. Finally, the third-order correlation integrals K3(Q2) are found to be significantly different from zero which implies the presence of genuine three-particle correlations in muon-nucleon interactions. © 1994.